Paediatric hearing aid management: a demonstration project for using virtual visits to enhance parent support. - Muñoz, Karen; Kibbe, Kristin; Preston, Elizabeth; Caballero, Ana; Nelson, Lauri; White, Karl; Twohig, Michael (International Journal of Audiology, 2017)
Objective: The purpose of this study was to explore the use of virtual visits to monitor hearing aid use with data logging measurements and provide parent support for hearing aid management. Design: A 6-month longitudinal case study design was used. Study sample: Four families and two providers participated. Results: Average hours of daily hearing aid use increased 3.5 h from the beginning to the end of the study period. Prior to receiving virtual visits, the parents and the clinicians generally indicated they were hopeful about the benefits of virtual visits including the frequency and convenience of the appointments but had some concerns about technical difficulties. These concerns diminished at the conclusion of the study. Conclusion: Virtual visits provided benefits to families including flexibility and timely access to support. The ability to collect data logging information more frequently was important for effective problem-solving to increase hearing aid use. Both parents and clinicians were accepting of tele-support. Parents and professionals would benefit from technology that allows them to access data logging information more easily and frequently.